2010
DOI: 10.1039/b927153h
|View full text |Cite
|
Sign up to set email alerts
|

Examination of axonal injury and regeneration in micropatterned neuronal culture using pulsed laser microbeam dissection

Abstract: We describe the integrated use of pulsed laser microbeams and microfluidic cell culture to examine the dynamics of axonal injury and regeneration in vitro. Microfabrication methods are used to place high purity dissociated central nervous system neurons in specific regions that allow the axons to interact with permissive and inhibitory substrates. Acute injury to neuron bundles is produced via the delivery of single 180 ps duration, λ=532 nm laser pulses. Laser pulse energies of 400 nJ and 800 nJ produce parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 32 publications
0
70
0
1
Order By: Relevance
“…13 Pulsed femtosecond laser microbeams have been used to produce axonal injury in vivo in animal models, which are attractive tools for cell microsurgery in vivo due to their ability to generate extremely localized damage zones in single cells. 1,32,35 However, the high cost and complex operation of these femtosecond laser systems makes them impractical for many researchers.…”
Section: Precisely Controlled Generation Of Axonal Injury Using Lasermentioning
confidence: 99%
“…13 Pulsed femtosecond laser microbeams have been used to produce axonal injury in vivo in animal models, which are attractive tools for cell microsurgery in vivo due to their ability to generate extremely localized damage zones in single cells. 1,32,35 However, the high cost and complex operation of these femtosecond laser systems makes them impractical for many researchers.…”
Section: Precisely Controlled Generation Of Axonal Injury Using Lasermentioning
confidence: 99%
“…Through precise control of the laser parameters, it is possible to cause either complete transection of neurites extending from neurons in culture or localized subaxotomy damage from which the neurites recover [8]. In a recent study, axons from embryonic rat cortical neurons were grown as oriented bundles using a patterned substrate and were completely severed using a 532 nm 180 ps laser microbeam [9]. Subsequent dieback and regeneration of these axons were studied.…”
Section: Introductionmentioning
confidence: 99%
“…44 Pulsed laser excitation has also been integrated with micro-channels to induce acute axonal injuries and such systems can offer high throughput results for drug screening to accelerate axonal recovery. 45 Co-culture microfluidic platforms when combined with micro-technologies to exert mechanical forces on seeded neurons, astrocytes and oligodendrocytes can also be developed to investigate the role of different neural cells in neuronal development, injury and recovery. 46 Potential tools: Progress in droplet microfluidics has enabled the generation of droplets having different sizes, composition and shapes.…”
Section: Micro-channels and Micro-patterningmentioning
confidence: 99%
“…108 Using surface patterning and fluidic resistance, axons can be preferentially separated from the dendrites, hence creating a model to study axonal growth, injury and recovery. 45,109,110 Nguyen et al utilized a vacuum-supplemented microfluidic channel array that models an array of 25 micropipette tips to apply mechanical tension to seeded neurons. 111 It was found that applying tension to the neurites enhanced their typical growth rates by 2-12x.…”
Section: Micro-technologiesmentioning
confidence: 99%